Risk analysis in concrete structure work using the hiradc method on the Hermina Ciawi Hospital project - Wijaya, Rivaldo (Calamity: A Journal of Disaster Technology and Engineering, 2024)
In the construction projects, a high risk of work accidents was found. Therefore, risk identification is very important to reduce the risk of work accidents afterwards. Risk identification begins with collecting research variables. These variables are then distributed to obtain probability and impact values ​​from respondents. The method used in this research is HIRADC (Hazard Identification Risk Assessment & Determining Control) which is assessed based on its frequency (probability) and the impact of the hazard (consequence/severity). This research aims to determine potential dangers and high-level risks. as well as risk control measures and the control of the risk. The research results show that there are 39 potential hazards with 10 high risks with determining control as per hierarchy for each hazard.